Enhancing Communicative Competence: Pragmatic Instruction in English Language Learning - Khalid, Shafaq; Maqbool, Saira; Nazli, Kishwer (Pakistan Languages and Humanities Review, 2025)
The main objective of this study is to explore the use of pragmatics in teaching and learning of English at undergraduate level. Pragmatics is known as the science of language in context. However, pragmatic competence is not frequently given more concern in instructional approach to languages where the focus is mainly on grammar and vocabulary. This paper explores how pragmatic features including speech acts, politeness strategies and cultural relevance influence the language acquisition process among undergraduate students. This research is a case study and data are collected through interviews, questionnaires and classroom observations to evaluate the practical dimension of students’ pragmatic learning context. The findings raise the awareness of pragmatic awareness in classroom practices. This research offer recommendations in relation to the identified gaps that will enrich the discourse on how best to promote communicative competence and integrate a holistic approach of meaning and form in teaching English.